The role of paranasal sinus fluid in determining drowning as the cause of death: A systematic review and meta-analysis - da Trindade, Rafael Queiroz; Duarte Morais Vieira, Maria Gabriela; Vieira, Raíssa Bastos; Vicentin-Junior, Carlos Antonio; Damascena, Nicole Prata; Santiago, Bianca Marques; Martins-Filho, Paulo Ricardo; Palhares Machado, Carlos Eduardo (Journal of forensic and legal medicine, 2023)
Drowning is a significant global cause of unintentional injury fatalities, and accurate forensic diagnosis of drowning remains a challenge due to the nonspecific nature of post-mortem findings obtained through classical autopsy methods. Our manuscript addresses this issue by focusing on the emerging use of paranasal sinus fluid as a valuable tool in determining the cause of death, specifically in distinguishing drowning from non-drowning cases. The study provided a comprehensive summary of available evidence from observational studies that compared findings in the paranasal sinuses between drowning and non-drowning victims, analyzing parameters such as the presence of fluid, fluid volume, and density. The study encompassed a total of 14 selected studies involving 1044 subjects and utilized rigorous risk of bias assessment and data synthesis techniques. The meta-analysis demonstrated a strong association between the presence of fluid in the paranasal sinuses and drowning (OR = 17.1; 95% CI 7.2 to 40.5; p < 0.001). In addition, drowning victims had a significantly greater volume of fluid (SMD = 0.8; 95% CI 0.5 to 1.2; p < 0.001) and lower fluid density (SMD = −1.4; 95% −2.5 to −0.4; p = 0.008) compared to non-drowning cases. The results support the utility of paranasal sinus fluid analysis as a valuable diagnostic method in cases where drowning is suspected but cannot be definitively confirmed through traditional approaches. •The presence of fluid in these air-filled cavities can indicate water aspiration during drowning.•There is a strong association between fluid presence in the paranasal sinuses and drowning.•Drowning victims had more fluid in the sinuses and lower fluid density compared to non-drowning cases.•Fluid in the paranasal sinuses is valuable to distinguish between drowning and non-drowning cases in criminal investigations.